2021
DOI: 10.1016/s2468-2667(21)00023-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternative income assistance schedules on drug use and drug-related harm: a randomised controlled trial

Abstract: Background The synchronised monthly disbursement of income assistance, whereby all recipients are paid on the same day, has been associated with increases in illicit drug use and serious associated harms. This phenomenon is often referred to as the cheque effect. Because payment variability can affect consumption patterns, this study aimed to assess whether these harms could be mitigated through a structural intervention that varied income assistance payment timing and frequency.Methods This randomised, parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…It is possible that clients are prioritizing other needed purchases during that week and are unable to come for pet food assistance. Previous research identified that income assistance payments in the DTES population that struggles with drug addiction coincides with drug-related harms, albeit the phenomenon is highly complex and nuanced ( 26 , 26 , 48 ). With that in mind, one possible way to mobilize this data to action could be to consider increasing the services offered during the third week of each month, for instance by distributing extra food to clients, to overcome this potential barrier to care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that clients are prioritizing other needed purchases during that week and are unable to come for pet food assistance. Previous research identified that income assistance payments in the DTES population that struggles with drug addiction coincides with drug-related harms, albeit the phenomenon is highly complex and nuanced ( 26 , 26 , 48 ). With that in mind, one possible way to mobilize this data to action could be to consider increasing the services offered during the third week of each month, for instance by distributing extra food to clients, to overcome this potential barrier to care.…”
Section: Discussionmentioning
confidence: 99%
“…The area within downtown Vancouver that houses and serves ~20,000 people with many experiencing financial hardships is generally regarded as the Downtown Eastside (DTES; Figure 1 ), which is ~4 km 2 and comprises the neighborhoods of Gastown, Chinatown, and Strathcona. A study in the area which focused on drug usage found that 26% of the population examined had an overdose or “life threatening event,” and that 3% passed away between October 2015 and January 2019 ( 26 ). Anecdotally, the prevalence of companion animals in the DTES of Vancouver is high, however metrics of that population are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The participants are followed using outreach and retention methods that promote interview completion and reduce loss to follow-up in the study population [ 90 ]. The outreach methods used by study staff include providing interview schedule cards and contacting participants prior to their due date to book an appointment via telephone, email, and mailed letters.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…The instrument was further validated through stakeholder consultation with community members and service providers, fieldtested among prospective study participants, and refined prior to the initiation of forma recruitment. The participants are followed using outreach and retention methods that promote interview completion and reduce loss to follow-up in the study population [90]. The outreach methods used by study staff include providing interview schedule cards and contacting participants prior to their due date to book an appointment via telephone, email and mailed letters.…”
Section: Data Collection and Follow-upmentioning
confidence: 99%
“…Computational methods include a gamut of different techniques including machine learning (e.g., deep learning, statistical learning, reinforcement learning), social network analysis, text and data mining (e.g., sentiment analysis, topic modelling, named‐entity recognition), agent‐based modelling, more flexible regression/estimation models (e.g., regression shrinkage and selection, Bayesian statistics, spatial regression models), advances in survey methods (e.g., survey experiments, optimum design, respondent‐driven sampling), and so on. Some sociologists in Canada have contributed directly to the development of particular methods (Alexander & Alkema, 2021; Andersen, 2008; Bignami‐Van Assche et al., forthcoming; Fosse & Winship, 2019; Fox, 2015; Fox & Andersen, 2006; Fu et al., 2020, 2021; Hayduk, 1996; Li et al., forthcoming; Miles, 2016; Nelson, 2020; Stecklov et al., 2018; Wellman et al., 2003, 2020), but more often sociologists have embraced and adapted methods developed by computer scientists, statisticians, and econometricians (Abul‐Fottouh et al., 2020; Boase, 2016; Das, 2022; Gallupe et al., 2019; Gruzd & Mai, 2020; Gu et al., 2021; Hogan & Berry, 2011; Howe et al., forthcoming; Kudla & Parnaby, 2018; Letarte et al., 2021; Li & Luo, 2020; McLevey, 2022; McMahan & McFarland, 2021; Quan‐Haase et al., 2021; Richardson et al., 2021; Roth et al., forthcoming; Shor & Miltsov, 2020; Shor et al., 2013; Silver & Silva, 2021; Smith, 2020; Sytsma et al., 2021; Veenstra & Vanzella‐Yang, 2022; Yuan et al., 2022).…”
mentioning
confidence: 99%